Ectopic ureter: A concise narrative review with anatomical and clinical commentaries - Krzysztof Balawender; Agata Wawrzyniak; Anna Pliszka; Anna Józefiak; Sebastian Siwak; Daniel Sokół; Edward Clarke; Agata Olszewska; Małgorzata Mazur; Agata Mazurek; Karolina Barszcz; Andrzej Żytkowski (Elsevier, 2022)
Background: The ectopic ureter is any single or duplex ureter that enters beyond the anatomical area of the triangle of the urinary bladder. Abnormal ureter opening is one of the rare defects resulting from abnormalities in fetal development. The present study focuses on an up-to-date narrative review of the clinical and anatomical aspects of the ectopic ureter and coexisting urinary tract abnormalities. Materials and methods: This review includes an analysis of the literature on the ectopic ureter and coexisting urinary tract anomalies. A query was conducted in electronic databases (PubMed, Web of Science, and ScienceDirect) to investigate the abovementioned topic. The literature search was based on the following criteria and keywords: ectopic ureter, duplication of the ureter, and ureterocele. The date and language of publication were not the exclusion criteria. Conclusion and outcome of the review: The ectopic ureter is one of the anomalies among congenital abnormalities of the kidney and urinary tract. In about four out of five cases, it coexists with other defects of the upper urinary tract, such as ureter duplication and ureterocele. Urinary incontinence is the main symptom of ectopic ureter among women due to the most common location of the ureter orifice below the bladder sphincter. It may be asymptomatic or mildly symptomatic in men and cause recurrent epididymitis or urinary tract infections. Treatment of this disease consists of constant observation by regular control visits, and when the abnormality becomes symptomatic, a surgical procedure should be performed. It should be underlined that after finding an anatomical defect of the urinary system, clinicians should consider whether it causes disturbing symptoms and whether its corrective maintenance operation will be beneficial to the patient.